(untitled) (AYUSHDHARA, 2025)
Lumbar Spondylosis, identified in Ayurveda as Dhatukshayjanya Kati Sandhigata Vata, is a progressive degenerative disorder affecting the lumbar spine. It is characterized by chronic back pain, stiffness, and reduced mobility, impacting the quality of life. Conventional treatment options, including NSAIDs and physiotherapy, provide symptomatic relief but fail to address the root cause. Ayurveda offers alternative solutions such as Marma therapy and Kati Basti, both of which aim to balance Vata Dosha and restore functional integrity. This study aims to conduct a comparative analysis of Marma Therapy on Katikataruna Marma versus Kati Basti in managing Dhatukshayjanya Kati Sandhigata Vata. A total of 60 patients were divided into two groups: Group A received Marma therapy, while Group B underwent Kati Basti. Pain reduction, lumbar mobility, and overall symptom relief were evaluated using the Visual Analog Scale (VAS) and the Straight Leg Raise (SLR) test. Results indicate that Marma therapy provided superior relief in pain intensity, spinal flexibility, and long-term management compared to Kati Basti. Statistical analysis using Wilcoxon Signed Rank Test, Paired T-test, and Mann-Whitney U Test confirmed a significant improvement in Group A. This suggests that Marma therapy is a more effective and holistic approach in treating Dhatukshayjanya Kati Sandhigata Vata. The findings contribute to the growing body of evidence supporting Ayurvedic treatments for spinal disorders. Further clinical studies are recommended to establish standardized protocols and enhance integration with modern medical practices.